CHANGES OF TRAFFIC MOBILITY AND ROAD TRAFFIC INJURIES IN MOSCOW DURING LOCKDOWN - Kirilina, Nadezda (Revista Inclusiones, 2020)
COVID-19 pandemic has quickly propagated all around the world and exerted significant effect on cities and traffic mobility. In this article, traffic data from various sources (State Center of Traffic Organization, Yandex, Citymapper) are analyzed to determine the changes of traffic mobility during lockdown in Moscow. The data of State Road Safety Inspectorate (GIBDD) were analyzed reflecting road traffic injuries on Moscow roads during lockdown. Despite the fact that in April there were significantly fewer vehicles and people on the roads than in 2019, road traffic injuries equaled to 10%, which was by 7.8 p.p. higher than in the previous year